Biological hazards of micro- and nanoplastic with adsorbents and additives - Ah Reum Hong; Ah Reum Hong; Jin Su Kim; Jin Su Kim (Frontiers Media S.A., 2024)
With the increased worldwide production of plastics, interest in the biological hazards of microplastics (MP) and nanoplastics (NP), which are widely distributed as environmental pollutants, has also increased. This review aims to provide a comprehensive overview of the toxicological effects of MP and NP on in vitro and in vivo systems based on studies conducted over the past decade. We summarize key findings on how the type, size, and adsorbed substances of plastics, including chemical additives, impact organisms. Also, we address various exposure routes, such as ingestion, inhalation, and skin contact, and their biological effects on both aquatic and terrestrial organisms, as well as human health. Additionally, the review highlights the increased toxicity of MP and NP due to their smaller size and higher bioavailability, as well as the interactions between these particles and chemical additives. This review emphasizes the need for further research into the complex biological interactions and risks posed by the accumulation of MP and NP in the environment, while also proposing potential directions for future studies.